Mechanical characteristics of graded origami bellows under axial tension - Zhang, Xinyi; Lu, Guoxing; Wang, Shenghai; Durandet, Yvonne (Frontiers in Physics, 2023)
In this study, the mechanical characteristics of graded origami bellows were numerically investigated and experimentally validated. Two graded geometric parameters were considered: pre-folding angle (θ) and height of layer (Le). Results show that the origami bellows with positive gradients exhibited a progressive deployment process from the top layer to the bottom layer. More than one deformation mechanism was triggered during deployment due to the graded parameters, indicating a mixed nonrigid deployment mode. The sensitivity of the deployment process and energy absorption efficiency of origami bellows to variation θ and Le was numerically investigated. The results showed that a large gradient of θ had a notable effect on the energy absorption efficiency. Both specific energy absorption (SEA) and mean tensile force (Pm) decreased as the gradient of θ increased. Although the gradient of Le was insensitive to the force response, the SEA decreased as the gradient of Le increased. The dynamic behavior of the graded models indicated that both the initial peak force and SEA were affected by the graded parameters. In general, the proposed graded origami bellows show a controllable deployment process and a stable force response under axial tension.